Design and optimization of dual band microstip patch antenna using slots pair - Alsaleh, Adel A.A.; Islam, Md. Rafiqul; Wan Nordin, Mimi Aminah; Al-Askari, Shadi (IEEE, 2016)
In the recent communication engineering,communication links require antennas which can operate more than one application band. Multiband antennas with microstrip patch are designed basically for mobile and aerospace applications, the reasons for that is that these antennas have very light weight, low profile and low power consumption. These antennas have many shapes to get the bandwidth and the gain required. This paper attempts to design Microstrip Patch Antenna to facilitate dual band operation using multiband design formula proposed in literature. Two frequencies of 1.8 and 2.4 GHz were designed for mobile and wireless LAN applications. Antenna has been designed and optimized using computer simulation technology CST electromagnetic simulator. Desired dual band has been achieved by very simple geometry of pair of slots. Pair of slots antenna has been fabricated and tested using vector network analyzer (VNA) in the Lab. Test result is found very good agreement with simulated result.